Characterisation of Ti/Al multilayered structures with slow positron beams applying a simplified positron depth distribution model - Naia, M. Duarte (2019)
This worked was support by the Portuguese Foundation for Science and Technology through the project POCTI/FAT/40924/2001 co-financed by European Union fund FEDER.